Inversor de cinco níveis baseado na célula de comutação de múltiplos estados tipo T - Cacau, Ronny Glauber de Almeida (2014)
This work presents the study, design and implementation of a multilevel converter based on T - type multi - state switching cell (5L - MSSC - T 2 ) for applications in low voltages and high currents. The proposed topology aims to extend the application of the multi - state switching cell (MSSC) to the structure of the three - level T - type converter, providing five levels in the output voltage before the filter and, consequently, a reduction of the harmonic content and higher output vol tage quality. Another feature of this topology is the uniform distribution of the total output current between the semiconductors of the converter, providing lower conduction losses and high efficiency. Furthermore , it is possible to reduce the weight and volume of magnetics, since the operating frequency of reactive elements is twice the switching frequency of the switches. A theoretical study with qualitative and quantitative analysis of the proposed inverter and the design methodology was performed . The control strategy implemented aims to control the output voltage and the DC bus voltages. The employed modulation technique is the conventional sinusoidal pulse width modulation (SPWM) . The validation of the topology is verified through simulation and exper imental results of a developed prototype for an output power of 5 kW